Variation of the diet of the sea urchin (Diadema mexicanum (Diadematoida: Diadematidae)) according to its size in the Eastern Tropical Pacific - Bogantes Retana, Andrea (2024)
We acknowledge the following persons that collaborated during the development of this work: C. Fernández, O. Breedy, C. Sánchez, S. Martínez, E. Gómez, A. Planas, V. Flores, O. Norzagaray, L.E. Calderón-Aguilera, A. Ayala, J. Carrión, L. Hernández, G. Ramírez, V. Vargas, J. Ramírez, and the Bezy, Sánchez-Camacho and García-Zuñiga families. We also thank the following institutions, organizations and companies: Centro de Investigación en Cien-cias del Mar y Limnología (CIMAR, Univer-sidad de Costa Rica), Universidad Autónoma de Baja California Sur (UABCS), Laborato-rio de Sistemas Arrecifales (LSA), Centro de Investigaciones en Ciencias Marinas (CICI-MAR), Universidad de Guadalajara, Centro de Investigación Científica y Educación Superior de Ensenada (CICESE), Universidad del Mar, Ministerios del Ambiente y Recursos Natura-les-El Salvador, Universidad de El Salvador, Smithsonian Tropical Research Institute, Liquid Jungle Lab, Charles Darwin Foundation, Hotel Pacífica, Mero Divers, Vallartec, Fundarrecife, and Reserva Biológica Isla del Caño, Parque Nacional Isla del Coco and Parque Nacional Los Cóbanos park rangers, MY Adventure crew, Instituto Costarricense de Turismo, Siste-ma Nacional de Áreas de Conservación-Costa Rica (SINAC), Autoridad Nacional del Ambi-ente- Panamá (ANAM), Hotel Punta Maren-co Lodge and Águila de Osa Inn. A special acknowledgement for their economic support for this research to Vicerrectoría de Investig-ación-Universidad de Costa Rica, Ministerio de Ciencia y Tecnología de Costa Rica (MICIT), Consejo Nacional para Investigaciones Cientí-ficas y Tecnológicas de Costa Rica (CONICIT), Consejo Nacional de Ciencia y Tecnología de México (CONACYT), Fonds Français pour l’Environnement Mondial (FFEM), Ecodesar-rollo Papagayo and Grupo Adelante.